2003
DOI: 10.1136/bjo.87.10.1272
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of corneal fibrotic wound repair at the LASIK flap margin

Abstract: Aim: To characterise temporal changes in corneal wound repair at the LASIK flap margin. Methods: 18 rabbits received monocular LASIK and were evaluated during 6 months using slit lamp and in vivo confocal microscopy. In three corneas, the exposed stroma was stained with DTAF. At various time points, corneas were processed for histology and stained for nuclei, f-actin, ED-A fibronectin, a-smooth muscle actin, TGF-b1, TGF-b2, TGF-b receptor II, and CTGF. Results: At day 1, leucocytes migrated from the conjunctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 30 publications
3
37
0
1
Order By: Relevance
“…For those exceptions, the flap edge was usually green, most likely having higher densitometry values due to minor fibrotic repair that occurs at the flap edge after primary treatment (Ivarsen et al, 2003). A study by Ori et al found that healthy corneas have a maximum densitometry value of 19 ± 4.4, which fell close to our pre-operative values that ranged from 21.8-27.2 (Ori et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…For those exceptions, the flap edge was usually green, most likely having higher densitometry values due to minor fibrotic repair that occurs at the flap edge after primary treatment (Ivarsen et al, 2003). A study by Ori et al found that healthy corneas have a maximum densitometry value of 19 ± 4.4, which fell close to our pre-operative values that ranged from 21.8-27.2 (Ori et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge, the only studies to evaluate microkeratome-created flap edges have been performed in animals. 11,13,14 The present study compared the morphology of corneal flaps created using 1 of 3 femtosecond lasers or a microkeratome. We examined flap thickness and side-cut angle using Fourier-domain optical coherence tomography (OCT) analysis.…”
mentioning
confidence: 99%
“…In accordance, a recent study in rabbits has demonstrated ReLEx flex to induce less wound healing and inflammation than FS-LASIK, particularly after high myopic corrections [49]. Whether this observation has any clinical consequence remains to be determined; however, wound repair after LASIK and, in particular, PRK has been extensively investigated and is known to influence the postoperative outcome [48,50,51].…”
Section: Experimental Studiesmentioning
confidence: 85%